Economics, development, and the quest for alternatives : essays in honour of professor M.A. Oommen - George, K. K.; Oommen, M. A., 1932-; Sankaran Nair, V., 1950-; Jacob, Jose (Concept Pub. Co., 1997)
Contributed articles with special reference to India.